Girl of nightmares - Blake, Kendare (A Tom Doherty Associates Book, 2014)
Months after Anna Korlov opened a door to Hell and sacrificed herself for seventeen-year-old ghost hunter Cas Lowood, persistent visions of Anna being tortured cause Cas to decide to save her as she once saved him.